Kerangka amalan terbaik penyampaian perkhidmatan pelanggan dalam kalangan pengusaha homestay di Malaysia - Abdul Mutalib, Siti Salwa (2022)
The Homestay program is one of the tourism forms that plays important role in bridging the economic gap, especially in rural communities. Most homestays in Malaysia are categorized as uncompetitive which are at a weak or moderate level. This is due, a reducing number of visitors staying at the homestays in several states. One of the problems identified is related to poor customer service that leads to customer dissatisfaction. Most studies have emphasized service quality, however, there are still limited studies on the aspect of customer service delivery homestays in Malaysia. Therefore, this study is aimed to develop a framework of customer service delivery best practices among homestay operators in Malaysia. The design of this research is mixed exploratory, which is a combination of qualitative and quantitative approaches. A total of nine experts were involved in this study and a thematic analysis was used to analyze the data. Furthermore, document analysis was conducted for data consolidation and subsequently implemented an expert agreement process. Then, a questionnaire was distributed to all the homestay operators in Malaysia to determine the suitability of the proposed domains and elements. All the responses were collected and analyzed using Principal Component Analysis (PCA) to determine the unidimensionality of the suggested domains and elements. This study found four important domains (customer relationship, skills, knowledge, attitude) and 18 derived elements that are unidimensional which are acceptable for the framework. The developed framework can be used as self-improvement guidelines for homestay operators and a reference for the development of training for homestay operators in Malaysia.